2019
DOI: 10.3168/jds.2019-16301
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of ruminal outflow of essential amino acids in dairy cattle

Abstract: The objective of this work was to update and evaluate predictions of essential AA (EAA) outflows from the rumen. The model was constructed based on previously derived equations for rumen-undegradable (RUP), microbial (MiCP), and endogenous (EndCP) protein outflows from the rumen, and revised estimates of ingredient composition and EAA composition of the protein fractions. Corrections were adopted to account for incomplete recovery of EAA during 24-h acid hydrolysis. The predicted ruminal protein and EAA outflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 154 publications
0
11
0
Order By: Relevance
“…Because the supply of Lys and His in the basal diets were only marginally below targets, it is plausible that supplies of Lys and His may have been adequate without the inclusion of either RP Lys or His. Variance in modelestimated supply of individual AA can be large (Fleming et al, 2019b); therefore, the true supply of Lys and His in the current study is unknown. Admittedly, the target for Lys and His supply are not well established, and suppling increasing amounts of Lys (Vyas and Erdman, 2009) or His (Zang et al, 2019) may increase milk production and milk component yield.…”
Section: Resultsmentioning
confidence: 97%
“…Because the supply of Lys and His in the basal diets were only marginally below targets, it is plausible that supplies of Lys and His may have been adequate without the inclusion of either RP Lys or His. Variance in modelestimated supply of individual AA can be large (Fleming et al, 2019b); therefore, the true supply of Lys and His in the current study is unknown. Admittedly, the target for Lys and His supply are not well established, and suppling increasing amounts of Lys (Vyas and Erdman, 2009) or His (Zang et al, 2019) may increase milk production and milk component yield.…”
Section: Resultsmentioning
confidence: 97%
“…However, compared to other amino acids, the PM's histidine content (including leaf, stem, and whole plant) was relatively low, which should be taken into consideration when a PM-based diet is supplemented with concentrates for dairy cows. Among the top five amino acids in the leaf and whole plant, leucine and lysine were the essential amino acids for dairy cows, making up for the deficiency that cows cannot synthesize these amino acids by themselves [40,41]. In short, PM's amino acid composition does not entirely meet the ideal amino acid requirements of dairy cows.…”
Section: Yield and Chemical Compositionmentioning
confidence: 99%
“…Therefore, differential degradation of individual AA is likely related to the differences in the structure and AA profile of different proteins within feeds. Recently, Fleming et al (2019) developed prediction equations for the flow of AA to the small intestine and reported that the flow of EAA, with the exception of Leu, was consistently overestimated. They attributed this overestimation to methodological problems in the analysis of AA, citing the "under-reporting of true flows in the literature due to recovery problems."…”
Section: Gargallo Et Al: Degradation Of In Vitro Fish and Blood Meal Amino Acidsmentioning
confidence: 99%